Type IV Hypersensitivity Reaction to Dermabond Prineo in Plastic Surgery Patients: A Report of 4 Cases - Alexander Ramirez-Folleco, MD; Paula Lancheros-Ramirez, MD; Daniel Guerrero-Calderón, MD; Andres Ramirez-Folleco, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Dermabond Prineo, a 2-octyl cyanoacrylate-based skin closure system, is widely used in surgical procedures, but reports of adverse effects remain limited. This study aimed to report and analyze 4 cases of type IV hypersensitivity reactions to Dermabond in plastic surgery patients. The study was conducted in a private hospital in Cali, Colombia, between 2022 and 2024. Four patients who underwent reconstructive surgery and presented type IV hypersensitivity reaction after the use of Dermabond were included. Variables such as time of onset of symptoms, number of Dermabond applications, and postoperative management were considered. A literature review was performed for the analysis. All patients developed type IV hypersensitivity reactions after Dermabond application. Symptoms included erythema, pruritus, and other localized signs. These reactions improved significantly after the withdrawal of Dermabond and treatment with topical corticosteroids. All patients had been previously exposed to Dermabond in previous procedures. Dermabond reexposure in sensitized patients may induce type IV allergic reactions. Early identification and treatment of these reactions is crucial.